Modal ethics: the role of counterfactuals in stoicism - Breen, EV (2020)
This paper argues that interpreting Stoic compatibilism through the lens of Chrysippus’ modal logic (specifically his account of counterfactual possibility) reveals a broader understanding of moral responsibility than is typically discussed. Moreover, this understanding suits the school’s emphasis on human nature and moral improvement. To the Stoics, the moral agent is considered responsible for all acts of assent (and thus all impulses, beliefs and thoughts) but modal responsibility goes beyond this. If the agent is considered responsible in the presence of a counterfactual opportunity to act otherwise - even in circumstances that she was not immediately able to control – then she is forced to consider the notion of internal consistency and temporalised understanding of external hindrance employed by Chrysippean possibility. Thus, moral responsibility understood this way encompasses an understanding of the agent’s nature as a being that is teleologically capable of virtue and a consideration of her future moral development. The paper attempts to consider the interweaving system of logic, physics and ethics in a holistic manner to reveal the full scope of Stoic responsibility.